KESULITAN BELAJAR SISWA DALAM BERPIKIR TINGKAT TINGGI BERDASARKAN TEORI NEWMAN - Safitri Wulandari (Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study aims to describe students' learning difficulties, especially at the elementary school level, in solving higher order thinking questions based on Newman's Theory. This research is a descriptive research. The subjects in this study were 29 students of class IV at SDN Sananwetan 2. The data obtained were in the form of descriptive test results and results from student interviews which were analyzed qualitatively. The results of the student test scores were grouped into three consisting of students with high abilities (test scores between 88-100), students with moderate abilities (test scores between 75-87), and students with low abilities (test scores between 0-74). Then the researcher randomly selected one student from each grouped category. The results of this study are that there are 7 high ability students, 14 medium ability students and 8 low ability students. Newman's theory states that the indicators of error are reading, understanding questions, transformation, process skills and solving processes. From the results of the students doing the test, it was found that there were different errors from each subject.